Development of conceptual design of car housing side mirror using intergrated approach - Hambali , Arep; Tajul Ariffin, Abdullah; Nurul Hidayah , Arshad (2012)
This paper presents the development of automotive car housing side mirror using integrated approach. The car housing side mirror was chosen to illustrate the application of integrated approach. Various product development stages were conducted which initially from market investigation to concept development stage. Conceptual design stage is a main design stage which is analytical hierarchy process (AHP) was selected as a decision making method to determine the most appropriate design concept. Finite Element Analysis (FEA) was employed to analysis design based on static analysis for determining the strength and performance of the design. The result shows design concept 3 (DC-3) is the preferred choice since it has the highest value among the five alternatives with a value of 0.4701 (47%).